2005
DOI: 10.1071/ar05022
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Acacia mearnsii tannins decreases methanogenesis and urinary nitrogen in forage-fed sheep

Abstract: The objective of this experiment was to assess the effects of a partial replacement of ryegrass (Lolium perenne) by red clover (Trifolium pratense) or alfalfa (Medicago sativa) supplemented with 0 or 41 g Acacia mearnsii extract (containing 0.615 g/g condensed tannins)/kg dietary dry matter on nitrogen turnover and methane release by sheep, using the respiration chamber technique. Across all variables, there was no significant interaction between basal diet and tannin supplementation. The partial replacement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
273
8
28

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(336 citation statements)
references
References 30 publications
27
273
8
28
Order By: Relevance
“…In the studies of Carulla et al (2005) and Grainger et al (2009), higher faecal N excretion and concomitantly lower urinary N excretion were observed without an effect on N retention. This was confirmed by the present study, in which the shift in N excretion was found in periods B2 and B3 for both experiments.…”
Section: A-cmentioning
confidence: 90%
See 1 more Smart Citation
“…In the studies of Carulla et al (2005) and Grainger et al (2009), higher faecal N excretion and concomitantly lower urinary N excretion were observed without an effect on N retention. This was confirmed by the present study, in which the shift in N excretion was found in periods B2 and B3 for both experiments.…”
Section: A-cmentioning
confidence: 90%
“…The authors suggested that the tannin dose administered was not high enough to decrease methane release. Carulla et al (2005) showed that methane release from lambs (25 kg BW) was reduced by up to 13% upon the addition of~2.9 g/kg BW 0.75 per day of an acacia extract (content of CT: 61.5 g/kg) to their diet. Methane release was measured on days 19 and 20 after starting supplementation; thus, it remains to be seen whether this effect can be retained over longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…Provided the confirmation of such effects in vivo, this could mean that such mixtures of high-quality and highphenolic forages could help to mitigate CH 4 without correspondingly extensively reducing ruminal nutrient utilisation. The mixtures would also prevent excessive degradation of protein into NH 3 . Whether or not non-additive effects of combining such plants can be recovered in vivo and on which compound interactions they mechanistically rely merits further studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the binary combinations, such non-additive effects were found only for C. papaya together with S. mahagoni and for C. hirta together with E. aquea (P, 0·05). With regard to NH 3 -related variables, non-additive effects (negative deviation; P,0·01) of all mixtures of C. papaya combined with the other plants were observed for NH 3 and NH 3 -N:dietary N. The magnitude of the effects was considerable with deviations of mostly more than 2 20 %. No such effect was found with combinations of the high-phenolic plants, except for the mixture of S. mahagoni and E. aquea.…”
Section: Non-additive Effects Of Using Plant Mixturesmentioning
confidence: 93%
“…Tannin supplements and tanniferous forages can be used for this purpose and have been shown to reduce urinary N as proportion of total N losses by 9.3% (Carulla et al, 2005) and 25% (Misselbrook et al, 2005a). Tannin use can also decrease N-release rate from manure, and thus affect manure-N availability for plant growth (Hristov et al, 2013).…”
Section: Mitigation Options For Manure Managementmentioning
confidence: 99%